ANALISIS YURIDIS PANDANGAN HAKIM PENGADILAN AGAMA GIRI MENANG TERHADAP EFEKTIVITAS PELAKSANAAN PUTUSAN NAFKAH PASCA PERCERAIAN - Ernawati, Ernawati; Humaedi, Humaedi (Jurnal Muhakkamah, 2019)
The percentage of livelihoods after divorce in the Divorce Decision for the Petitioner (husband) in the Giri Menang Religious Court in the last 2 (two) years (in 2017 and 2018) is still very minimal. This was due to the fact that there were many divorce divorce cases which were not attended by the Respondent (wife) in their examination (the court), so that the case was decided by verstek (without the presence of the Respondent / wife). Form of consideration and legal basis for the Panel of Judges of the Giri Menang Religion Court in dropping the Decision on the post-divorce livelihoods of the divorce divorce case to the Respondent (husband. In 2017, the effectiveness of the implementation of the decision reached 83.33% and in 2018 (the period of January to August 2018 reached 75.00%. Thus, the Divorce Divorce Decision in which there was liability after divorce at the Giri Menang Religious Court. classified as effective The effectiveness of the Divorce Divorce Decision in which there is a post-divorce income burden in the Giri Menang Religious Court is influenced by 3 (three) main factors.